Analisis Pengaruh Indeks Ketahanan Pangan, Bantuan Pangan Non Tunai, dan Produksi Beras Terhadap Tingkat Kemiskinan di Indonesia (Lembaga Pengembangan Kinerja Dosen, 2026)
Poverty is a multidimensional problem that remains a major challenge in economic development in Indonesia. This study aims to analyze the effect of the Food Security Index, Non-Cash Food Assistance (BPNT), and Rice Production on poverty levels in Indonesia. This study uses panel data from 34 provinces during the 2019–2022 period. The analytical method used is panel data regression with the Fixed Effect Model (FEM) approach. The results show that the Food Security Index, BPNT, and Rice Production simultaneously have a significant effect on poverty levels. Partially, BPNT has a negative and significant effect on poverty levels, indicating that food assistance programs play an important role in reducing poverty levels. Meanwhile, the Food Security Index and Rice Production do not show a significant effect on poverty levels. These findings indicate that poverty alleviation is more effective through targeted food-based social interventions than through improving macro-level food security indicators or increasing rice production alone. Therefore, poverty alleviation policies need to focus on strengthening and expanding inclusive food assistance programs and improving food distribution and access for poor households.